Ethnomathematics in Traditional Farming Systems in Pegalongan Village, Patikraja - Nurbaiti, Idhata; Kusno, Kusno (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2025)
Pegalongan village is located in the south of Purwokerto city and the majority of the population work as farmers. Rice farming in this area is an important part of local culture and tradition, as well as a major source of livelihood for the local community. The purpose of this study is to find the mathematical elements hidden in the operation of rice farming and the philosophical value contained in it. To understand how rice farming communities use mathematics in their cultural context, this study used a descriptive qualitative ethnographic approach. The research involved farmers and farm labourers. The focus of the research includes the planting land, and the process of planting rice, the cultivation of the farmers in the form of mimiti and mbawoni. Data was collected through direct observation of farmers, documentation, and in-depth interviews. Data were analysed thematically to find key themes related to ethnomathematics in rice cultivation. These themes included the use of mathematics in agricultural activities, the use of traditional tools and units of measurement, and agricultural processes rooted in local culture. The study also emphasised that ethnomathematics should be part of the education curriculum to improve students' understanding. The results showed that mathematical concepts such as arithmetic, and measurement can be applied in land cultivation. The results show that local knowledge is critical to agricultural practices, and how ethnomathematics can be incorporated into the education curriculum to improve students' understanding of mathematics in a cultural context.